A comparative fiqh in Islamic finance: analysis for bitcoin issues in Islamic perspective / Ainul Fatinah Dayini Mohd Sabri … [et al.] - Mohd Sabri, Ainul Fatinah Dayini; Norlizal, Norain Husna; Roslan, Ruhil Farhanim; Sabri, Nur Huda Syazana; Abdul Moin, Nur Asyiqin (2023)
The public has been debating the currency problem on a regular basis recently. In addition to operating on a decentralized network known as the blockchain, which acts as a public ledger maintaining a record of all transactions ever made with the currency, Bitcoin also becomes one of the commodities tools. Although Bitcoin has been introduced to the public since 2009, it is still not trusted as an investment tool. Islamic teachings do not refuse to make changes or improvements to existing things. Existing improvements are highly encouraged for the benefit of the Muslim community in knowing the law for all matters. However, every improvement must be referred to Scholars and experts in determining the law, especially Bitcoin. An article in Berita Malaysia Now online, states that Malaysia does not recognize cryptocurrencies including Bitcoin and Ethereum as legal tender for daily transactions. Cryptocurrencies are not suitable for use as payment instruments because they do not exhibit the universal characteristics of money. (Malaysia Now)